Exploring the Master Narrative: Racial Knowledge and Understanding of Language and Literacy Pedagogy for Special Education Teacher Candidates. Issue 1 (2nd January 2019) - Banks, Joy; Gibson, Simone
Abstract: Researchers have revisited the influence of African American English many times within extant scholarship over the past 4 decades. However, the resulting pedagogical developments within teacher training programs are inadequate. Through a survey of literature of relevant topics, this article provides a framework regarding training for preservice teachers to ensure that they understand the historical intersectionality of race, gender, and language, especially when educating African American males. We believe the dismal underperformance of African American males and their significant disproportionality in special education should enliven the focus of reform efforts on the instructional and dispositions toward nonstandard English, such as African American English, which influence the fidelity of instruction.